THE EFFECTIVENESS OF USING STRUCTURED DYADIC METHOD (SDM) IN TEACHING READING NARRATIVE TEXT SMAN 2 AIKMEL: EFEKTIVITAS PENGGUNAAN METODE DYADIK TERSTRUKTUR (SDM) DALAM MENGAJARKAN MEMBACA TEKS NARATIF SISWA SMAN 2 AIKMEL - Diah Afriani; Burhanuddin (Jurnal Prasasti Ilmu, 2026)
This study was conducted to determine if the Structured Dyadic Method (SDM) was effective in teaching first-year students at SMAN 2 Aikmel how to read narrative texts. The study was an experiment, and the design used was the Pre-test-Post-test Control and Experimental Group Design. The study included first-year students from SMAN 2 Aikmel, and there were five classes in total. Two classes were selected as samples using cluster random sampling. The first class, X.IPA-1, was the Experimental Group and was taught using the SDM method. The second class, X.IPA-2, was the Control Group and was taught using the traditional method. The sample of research was 82 students. The data was checked using a statistical method called the T-test. The analysis results show that the average score for the Experimental group was 69.33 and for the Control group was 58.3. The t-test value (to) is 1.838, and the t-table value (tt) from a table with 80 degrees of freedom at a 5% significance level is 1.664. Since the to value is greater than the tt value, this indicates a statistically significant difference between the two groups. A researcher calculated the difference score between to and tt, and it came out to be 0.174. Because students who were taught using the structured dyadic method scored better on their achievement test compared to those who were taught reading English texts through Pre-Questioning or the traditional teaching method. So, the alternative hypothesis was accepted, and the null hypothesis was clearly rejected. It can be said that the Structured Dyadic Method (SDM) works well for teaching reading narrative texts to first-year students at SMAN 2 Aikmel.